The potential application of stem cell in dentistry - Ketut Suardita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Stem cells are generally defined as cells that have the capacity to self-renewal and differentiate to specialize cell. There are two kinds of stem cell, embryonic stem cell and adult stem cells. Stem cell therapy has been used to treat diseases including Parkinson’s and Alzheimer’s diseases, spinal cord injury, stroke, burns, heart diseases, diabetes, osteoarthritis, and rheumatoid arthritis. Stem cells were found in dental pulp, periodontal ligament, and alveolar bone marrow. Because of their potential in medical therapy, stem cells were used to regenerate lost or damage teeth and periodontal structures. This article discusses the potential application of stem cells for dental field.